Implementasi Aplikasi E-Office di Badan Pendapatan Daerah Provinsi Sulawesi Utara - Dahlan, Efraim; Mangundap, Nathania; Putra, Edson; Atteng, Olvie (LPPM Universitas Potensi Utama, 2023)
In the Regional Revenue Agency of North Sulawesi Province (BAPENDA), the process of sending letters still uses the manual method. By using the manual method, letters that have been sent cannot be tracked with certainty on where the letters are. This obstacle becomes a challenge to the organization in carrying out fast and precise business processes. So, the researcher was given the task of making an E-Office application. The purpose of making the application can simplify and develop the process of sending the letter. In short, the E-Office application that was created has the aim of facilitating business processes for correspondence within BAPENDA so that it can be carried out quickly, precisely, and flexibly. This application will be made based on the letter management SOP that applies at BAPENDA. Research on required applications uses the Modified Waterfall model, which is the result of a modified Waterfall method that is more flexible than the Waterfall model. The type of data taken is qualitative data, in which data is taken using interviews with parties involved in the process of business correspondence and dispositions. Information from the interview will be recorded and used to design the application to suit the needs & desires of the organization. The E-Office application will provide a new experience for organizations in carrying out correspondence business processes with convenience such as the user being able to find out where the letter has been, sending it is also made easier because it can be done wherever the user is, as long as they have an internet connection, it also makes it easier to view file and letter history with shipping details, etc. By implementing this application, it can encourage organizations to compete with other organizations in utilizing internet technology as an intermediary for business processes.